GLOBALISASI BANGSA ARAB DI DUNIA MELAYU: Dinamika Aksara Arab Melayu di Indonesia - Siti Aisyah (Khazanah: Jurnal Sejarah dan Kebudayaan Islam, 2017)
The Malay people made Arabic as the medium of instruction in the form of writing by the Malay community. The use of this script is known as Malay Arabic script by adding some Arabic letters by adjusting the sound with Malay language. The first stage of this writing as a communication in trade between the people of Indonesia with Arab traders, then the writers use it as script writing in Malay language. This writing continues to use it as the medium of instruction in Islamic education and teaching to the public. Then the scientists and scholars use it as well as writing characters in writing religious books such as fiqh, tafseer, hadith and tarekat and other writings. After that Malay Arabic script has become a national script of Malay society, including in Indonesia. The Malay Arabic script was used as a newspaper and magazine literature until the arrival of Europeans to the archipelago. Slowly after that Malay Arabic script is no longer used as a national writing script by Malays society including Indonesia.